"Human Again": The (Unrealized) Promise of Basic Income in Ontario. Issue 7 (10th November 2019) - Hamilton, Leah; Mulvale, James P.
ABSTRACT: Neoliberal social assistance programs are broadly seen as inadequate and intrusive. This phenomenological analysis compares social assistance in Ontario, Canada, and a recent pilot project to test basic income as an alternative method of enabling economic security and social participation via qualitative interviews with pilot recipients who had previously received traditional assistance. Results indicate a desire to be financially independent, but that the conditionality of traditional programs had negative repercussions including work disincentives and deleterious bureaucratic hurdles. Respondents reported that basic income has improved their nutrition, health, housing stability, and social connections; and better facilitated long-term financial planning.